(untitled) - Kuzmeski, Maribeth (Hoboken, N.J., 2009)
Learn the relationship-building secrets that lead to lifelongclients, repeat customers, and endless referrals In today's commoditized marketplace, no matter what product orservice you sell, there's probably someone somewhere able to offerit cheaper, faster, and maybe even better. So how do youdifferentiate yourself from your competitors? The Connectorsshows that the only thing that truly sets you apart is the qualityof your relationships with your clients and customers. Everyone knows that relationships are important in business. Yetmost people would admit that their relationships could bebetter-but don't spend time working on the underlyingskills. This book explains how to develop better, more profitableconnections-as illustrated proven by some of theworld's most successful professionals. Even if you're not a"people person," you can dramatically grow yourbusiness or your career through a few simple approaches torelationship-building. The Connectors presents a five-step methodology that leadto lifelong clients, repeat customers, and endless referrals.Inside, you'll learn how to: Stop networking and start truly connectingCreate an avalanche of referrals and an army of happycustomersBecome a "connector," even if you've never been a "peopleperson"Find your social IQ-and improve itPut relationship-building principles to work dailyFocus on others and reap the rewards yourselfAsk the right questions-and sell without sellingDifferentiate yourself through the impact you have onothers In The Connectors, Maribeth Kuzmeski, founder of Red ZoneMarketing, LLC, and consultant to Fortune 500 firms, shows you howto build profitable, long-lasting business relationships.
Keywords: Giao tiếp kinh doanh,Business communication